AI Capabilities as Mediators in Marketing Innovation: A Cross-Cultural Study of Technology Features and User Engagement Among Generation Z in Indonesia and Hungary - Tumiwa, Johan Reineer; Paat, Franda Benedicta; Roring, Ferdy; Nagy, Peter; Nagy, Adrian (Jurnal Ilmiah PLATAX, 2026)
This study investigates the mediating role of AI capabilities in the relationship between technology features and user engagement among Generation Z, with a cross-cultural focus on Indonesia and Hungary. The aim is to explore how cultural and technological contexts shape marketing innovation and user behavior. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) to analyze survey data from 743 Generation Z respondents (415 in Indonesia and 328 in Hungary). The study examines direct and mediated relationships between technology features, AI capabilities, and user engagement, and tests cross-cultural differences. The results reveal that AI capabilities significantly mediate the effect of technology features on user engagement, with notable differences between the two countries. Indonesian Gen Z emphasizes the direct and mediated effects of technology features, leveraging immersive and interactive platforms, while Hungarian Gen Z prioritizes ethical and sustainability-driven AI solutions as key drivers of engagement.  The study is limited to Generation Z in two countries, and future research could expand the scope to include other generational cohorts and regions. Longitudinal studies and behavioral data could also enhance the understanding of evolving user engagement dynamics. The findings highlight the importance of integrating AI-driven personalization, interactivity, and predictive analytics into marketing strategies to enhance engagement. Businesses targeting Gen Z should tailor their approaches to specific cultural and technological contexts, leveraging immersive technologies in Indonesia and sustainability-focused AI in Hungary. This research underscores the potential of AI and technology features to shape ethical and sustainable consumption patterns among Generation Z, informing corporate social responsibility and digital marketing practices. The study provides a quantitative hierarchy of relationships between technology features, AI capabilities, and user engagement, validated across culturally diverse contexts. It offers actionable insights for businesses and contributes to the theoretical understanding of cross-cultural technology adoption and marketing innovation. Keywords: Generation Z, AI Capabilities, User Engagement, Technology Features, Cross-Cultural Analysis